2017
DOI: 10.1109/tip.2017.2695887
|View full text |Cite
|
Sign up to set email alerts
|

A General Framework for Edited Video and Raw Video Summarization

Abstract: In this paper, we build a general summarization framework for both of edited video and raw video summarization. Overall, our work can be divided into three folds. 1) Four models are designed to capture the properties of video summaries, i.e., containing important people and objects (importance), representative to the video content (representativeness), no similar key-shots (diversity), and smoothness of the storyline (storyness). Specifically, these models are applicable to both edited videos and raw videos. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…As a whole, eleven baselines are employed here for comparison, including: STIMO [26], VSUMM [10], SumTransfer [7], SUM-GAN [13], SeqDPP [6], LSTM [15], TVSum [8], Li et al [14], MSDS-CC [27], LLR-SDS [28], and Online Motion AE [9]. The results from all of the baselines [26,10,6,7,13,14,15,8,27,28,9] are obtained from those reported in their papers.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a whole, eleven baselines are employed here for comparison, including: STIMO [26], VSUMM [10], SumTransfer [7], SUM-GAN [13], SeqDPP [6], LSTM [15], TVSum [8], Li et al [14], MSDS-CC [27], LLR-SDS [28], and Online Motion AE [9]. The results from all of the baselines [26,10,6,7,13,14,15,8,27,28,9] are obtained from those reported in their papers.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 99%
“…Lastly, we compare the proposed method with seven baselines on the TVSum dataset, including, SUM-GAN [13], LSTM [15], TVSum [8], Li. et al [14], MSDS-CC [27], LLR-SDS [28], and Online Motion AE [9] as shown in Table III. Our approach which combines the temporal encoding by rank pooling, near-duplicate frame removal by ITQ and peaksearching by SNIP can attain the best performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain processing pipelines have also been proposed to address the changing environmental illumination conditions [2]. Scene recognition and video summarization have been also proposed based on machine learning techniques and RGB data [6,7].…”
Section: Introductionmentioning
confidence: 99%